The - Aulya Putri Narayany; Raden Budi Hendaris (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Local government performance is a vital indicator of fiscal decentralization success in Indonesia, shaped by institutional and structural factors. This study examines the effects of capital expenditure, local government size, legislative size, and financial reporting quality on the performance of 35 regency and municipal governments in Central Java from 2017 to 2023. Using a descriptive quantitative approach with multiple linear regression on secondary data, results show that capital expenditure significantly improves performance by 35.1%, local government size by 1.8%, while legislative size has a negative effect of 3.8%. Financial reporting quality has no significant impact. Collectively, the four variables contribute 36.6% to performance. These findings align with institutional theory, underscoring the need to match external demands with internal capabilities. The study offers policy recommendations to enhance fiscal governance and strengthen the institutional effectiveness of local governments sustainably.